Zastosowanie dominacji probabilistycznych do selekcji ryzykownych papierów wartościowych - Styczeń, Anna (Applying Probability Dominance in Selection of Risk Securities, 2007)
For a long time scientists have been working on the subject of decision making. This paper concerns the problem presented in the publication "Probability Dominance in Random Outcomes" by C. Wrather and P.L Yu in 1882. Probability dominance can be used to compare variable data according to probability taking the appropiate values. The paper presents the problem of probability dominance and its values.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1167, s. 244-254